PERAN GURU PAI DALAM PENGIMPLEMENTASIAN KURIKULUM MERDEKA DI SD N 77 DESA TELADAN - Karliana Indrawari; Intan Berlian; Nadia Obella; Novan Dwi Putra; Rasmiyana (CV. ALIM'SPUBLISHING, 2023)
Curriculum is a tool used to achieve educational goals used by schools dynamically and progressively. This study discusses the role of PAI teachers in implementing the Independent Curriculum at SDN 77 Teladan Village, this research includes using field research with a qualitative approach by observing existing data in the field using qualitative data analysis methods. In this research, the main data sources that were determined to obtain data according to the problems to be studied were: Principals of SDN 77 Teladan Village, and Islamic Religious Education Teachers. Meanwhile, secondary data sources or data that are indirectly obtained from documents or other people who provide data indirectly. The results of the study showed that: The role of PAI teachers in implementing the Independent Curriculum at SDN 77 Teladan Village has not been carried out optimally. The role of the Islamic Religious Education teacher in the preparation and implementation of the evaluation has not been carried out properly. This was obtained from the answers of the informants who stated regarding the Role of the PAI Teacher in implementing the Independent Curriculum, the results obtained were that from preparation to evaluation it had been carried out in accordance with the Free Curriculum guidelines, but there were also obstacles in implementing the Independent Curriculum which were obtained by researchers from informants and observations, which being an obstacle for PAI Teachers in implementing the Independent Curriculum that one of the obstacles is the facilities and infrastructure that are still inadequate and the media provided by the school so that the teaching and learning process is carried out is still not optimal. As well as the need for an evaluation of the socialization of the independent curriculum so that the goals of the independent curriculum can be implemented even better.